Kinetics of Carbothermic Reduction of Synthetic Chromite - Wang, Yaxian; Wang, Lijun; Yu, Jipeng; Chou, Kuo-Chih (Journal of Mining and Metallurgy, Section B: Metallurgy, 2014)
In order to optimize the current reduction process of chromite, a good knowledge of reduction mechanism involved is required. The basic component in chromite ore is FeCr2O4, thus, kinetic investigation of synthetic FeCr2O4 with different amount of carbon were carried out in the temperature range of 1473K to 1673K under both isothermal and non-isothermal mode. The iron can be easily reduced compared with chromium. And higher reduction degree of chromite can be achieved by increasing temperature and carbon content. With the supporting of X-ray Diffraction and Scanning Electron Microscope methods, the formation of metallic products followed the sequence: Fe-C alloy, (Fe,Cr)7C3and Fe-Cr-C alloy. Kinetics analysis showed that the first stage was controlled by nucleation with an apparent activation energy of 120.22kJ/mol, while the chromium reduction was controlled by gas diffusion with an apparent activation energy of 288.48kJ/mol.
Keywords: kinetics; chromite; carbothermal reduction